Factors that predict evidence use by Australian perioperative nurses - Jed Duff; Margaret Butler; Menna Davies; Robyn Williams; Jannelle Carlile (Journal of Perioperative Nursing)
Evidence-based practice has been demonstrated to positively impact patient outcomes; unfortunately, there are many factors that hinder the use of research evidence by healthcare clinicians. Our previous study reported a multisite survey assessing Australian perioperative nurses knowledge, practice, attitude, and perceived barriers to evidence use. This subsequent analysis used univariate and multivariate binary logistic regression with odds ratios (OR) and 95% confidence intervals (CI) to compare individual nurse and organisational characteristics with high evidence-based practice (EBP) use. Two individual nurse characteristics found to be related to EBP were postgraduate qualifications (OR 1.69, 95% CI 1.07–2.6, p=0.02) and previous research experience (OR 1.9, 95% CI 1.6–2.4, p=0.01). Organisational characteristics related to EBP included access to the internet (OR 2.04, 95% CI 1.3–3.0, p=0.001) and access to ongoing EBP education (OR 1.6, 95% CI 1.1–2.5, p=0.01). Previous research experience (OR 1.6, 95% CI 1.0–2.3, p=0.01) was the only independent predictor of EBP. Given our finding, we suggest that considerably greater effort be made to facilitate nurses involvement in research studies in the perioperative setting.